Asas Keadilan dan Kepatuhan Hukum: Kajian Komparasi Antara Hukum Pidana Positif dan Hukum Pidana Islam - Waqiatul Masyruroh; Moh Ardiyansyah (At-Tafakur: Jurnal Ilmu Syari'ah dan Hukum, 2024)
Criminal law is generally derived from Western legal systems, which focus on a set of principles aimed at protecting public interests and maintaining social order. In contrast, Islamic criminal law, based on the teachings of the Qur'an and Hadith, emphasizes a holistic approach to justice that encompasses moral and spiritual aspects, with the primary goal of protecting the maqasid al-shariah (the objectives of Sharia), which include the preservation of religion, life, intellect, lineage, and property. This study aims to analyze how the principles of criminal law affect society in the context of justice and compliance with the law. Through a comparison of these two sets of principles, the study seeks to provide an understanding of the application of conventional criminal law and Islamic criminal law in societal life. This research employs a qualitative method with a normative approach, and the findings indicate that although there are fundamental differences between Western and Islamic criminal law principles, both share the same objective of upholding justice and maintaining social order